Derivative proportional control and first order control with pole placement for a servopositioner electropneumatic - Silva, Esly César Marinho; Oliveira, Benedito Santana; Riul, José Antônio; Silva, Simplício Arnaud (Revista Ciências Exatas, 2008)
The pneumatic actuators have been widely used in industrial process because of their good relation between power, speed and acceleration when compared to electric and electronic mechanisms, besides their low cost for maintenance. In order to take advantage of the use of these actuators, together with the enhancement of the computer technology, the number of research projects about controllers has increased aiming at the overcoming of the non-linearity of the system, due to compressibility, low air stiffness, friction and etc., and at the improvement of the robustness of the responses of these actuators. This work has in view to evaluate the performance of an electro-pneumatic servopositioner, using techniques of poles allocation, under the action of two controllers: a derivative proportional controller with filter and another phase delay with performance index basis ITAE. After the identification of the plant, simulations and experiments are made to the diverse reference positions. The responses of the system, under the actions o theses controllers, in the time domain, are compared and analyzed to the same work conditions.